Proposals for the development of control means of the technical condition of unmanned aircraft - Borisenko, M.; Utyuzhok, S. (National Academy of the National Guard of Ukraine, 2022)
The synthesis of optimal parameters of the input test signal for monitoring and diagnosing the technical condition of the UAV electronic equipment is to solve the variational problem of calculating the maximum (minimum) value of the functional that characterizes the class of test signals. Mathematical models of possible limitations in the synthesis of optimal parameters of input test signals are substantiated.
Keywords: technical condition; unmanned aircraft